DRY MATTER YIELD AND COMPETITIVENESS OF ALANG-ALANG (Imperata cylindrica) AND GUINEA GRASS (Panicum maximum) IN INTERCROPPING - M. Rusdy (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
The objectives of this experiment were to determine dry matter yield and competitiveness of alang-alang (Imperata cylindrica) and guinea grass (Panicum maximum) in intercropping. The experiment was arranged in factorial combinations of four planting proportions, two levels of nitrogen fertilization and three harvesting intervals with three replications. Planting proportions were 0, 33.3, 66.7, and 100% of alang-alang (planting densities of 0, 1, 2 and 3 plants/pot) combined with 100, 66.7, 33.3, and 0% of guinea grass (planting densities of 3, 2, 1 and 0 plants/pot). The plants fertilized with nitrogen fertilizer at the doses of 0 and 250 kg/ha and harvested at intervals of 30, 45 and 90 days. Results of experiment showed that as planting proportion of alang-alang increased in the mixtures, total dry matter yield of mixed plants decreased. N fertilization increased dry matter yield in both species, but guinea grass was more responsive than alang-alang. Regardless of planting proportion and nitrogen fertilization, increasing harvest interval decreased dry matter yield of guinea grass – alang-alang mixture. Intercropping system gave substantially higher yield advantage over sole cropping in terms of land equivalent ratio with the maximum value achieved when guinea grass – alang-alang mixture planted at the ratio of 2 : 1, fertilized with N and harvest monthly. In intercropping system, guinea grass appeared to be the dominant crop as indicated by its higher values of relative crowding coefficient and positive sign of aggressivity index. It reflects that guinea grass grown in association with alang-alang utilized the resources more aggressively than when alang-alang grown alone.